2019
DOI: 10.1002/nur.21980
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Korean version of the Occupational Fatigue Exhaustion Recovery Scale in a nurse population

Abstract: Most nurses in Korea work rotating shifts, an important contributor to fatigue. The Occupational Fatigue Exhaustion Recovery (OFER) Scale assesses work‐related fatigue among nurses. In this study, we aimed to translate and culturally adapt the Korean version of this scale (OFER‐K) with nurses working rotating shifts in Korea. Instrument adaptation was performed using committee‐based translation, cognitive interviewing, and expert panel interviewing. Criterion validity, convergent validity, construct validity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 45 publications
1
46
1
2
Order By: Relevance
“…More than half of the DCRNs had moderate to high levels of chronic fatigue. Levels of chronic fatigue in all nurses were higher than those found in a sample of New Zealand intensive care nurses working 12‐hour shifts (Yu et al, 2019) but lower than those found in Lebanese direct care nurses (Sagherian et al, 2017) and in Korean direct patient care nurses working rotating shifts (Min et al, 2019a). It is interesting to note that the differences in levels of acute and chronic fatigue in DCRNs compared with non‐DCRNs were small, and those group differences disappeared once other factors were considered in the regression models.…”
Section: Discussioncontrasting
confidence: 52%
“…More than half of the DCRNs had moderate to high levels of chronic fatigue. Levels of chronic fatigue in all nurses were higher than those found in a sample of New Zealand intensive care nurses working 12‐hour shifts (Yu et al, 2019) but lower than those found in Lebanese direct care nurses (Sagherian et al, 2017) and in Korean direct patient care nurses working rotating shifts (Min et al, 2019a). It is interesting to note that the differences in levels of acute and chronic fatigue in DCRNs compared with non‐DCRNs were small, and those group differences disappeared once other factors were considered in the regression models.…”
Section: Discussioncontrasting
confidence: 52%
“…According to Min and colleagues [ 62 ], nurses perform in multifaceted circumstances that embrace the highest experience and capability in displaying a patient-oriented attitude and providing nursing care. The challenging work atmosphere in the hospital places a great deal of pressure on nurses’ shoulders.…”
Section: Discussionmentioning
confidence: 99%
“…Exhaustion was a concept for nurses to express their thoughts and impressions during coronavirus in this current research study. Nurse exhaustion is a “work-related situation that ranges from severe to long-lasting in nature and can generate an overwhelming sense of tiredness, reduced dynamism, as well as tiredness resulting in impaired physical functioning, cognitive functioning, or both” [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Korean version of the Occupational Fatigue Exhaustion/Recovery Scale (OFER-K), which consists of 15 items (Min et al, 2019), was used to measure nurses' occupational fatigue and recovery. The scale involved three subscales: acute fatigue (OFER-AF), chronic fatigue (OFER-CF), and intershift recovery (OFER-IR).…”
Section: Occupational Fatigue and Recoverymentioning
confidence: 99%